HARMONI: "Hidup Berbagi, Mengatasi Kesepian dan Konflik" Sebagai Upaya Membangun Keterhubungan Sosial di Kalangan Lansia - Tiara Nurmaritza Putri; Kadek Deandra Alea Casta; I Made Risky Saputra; I Putu Angga Arya Prasetya; Putu Wahyu Mahadiva Sajna Sandi; Ni Luh Indah Desira Swandi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study addresses the psychosocial challenges of loneliness and social conflict among elderly residents at Panti Sosial Tresna Werdha Wana Seraya. The research aims to develop and evaluate the effectiveness of the HARMONI intervention program in reducing loneliness and improving social interaction. Employing a quantitative pre-experimental one group pretest-posttest design, the study involved six purposively selected elderly participants. Data were collected using the UCLA Loneliness Scale, non-participant observation, and semi-structured interviews. Data analysis included normality tests and paired samples t-tests for quantitative data, and triangulation for qualitative data. Results showed a statistically significant decrease in loneliness scores after the intervention, with participants demonstrating increased social engagement and positive behavioral changes. The findings suggest that the HARMONI program is beneficial for enhancing social connectedness and emotional well-being among institutionalized elderly. Future research should involve larger samples and longer intervention periods to strengthen generalizability and practical application.